2019
DOI: 10.3390/beverages5030048
|View full text |Cite
|
Sign up to set email alerts
|

Grape Infusions: The Flavor of Grapes and Health-Promoting Compounds in Your Tea Cup

Abstract: Traditionally, tea, a beverage made from the processed leaves of the tea plant, Camellia sinensis, and herbal infusions have been primarily consumed for their pleasant taste. Nowadays, they are also consumed because they contain nutraceutical compounds, such as polyphenols. Grapes and grape/wine sub-products such as non-fermented/semi-fermented or fermented grapes, skins, and seeds are a rich source of health-promoting compounds, presenting a great potential for the development of new beverages. Therefore, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 91 publications
0
22
0
Order By: Relevance
“…Due to their abundance in vegetables and MAPs, the study of phenolic compounds’ (simple phenolics, coumarins, lignans, flavonoids, isoflavonoids, anthocyanins, proanthocyanidins, and stilbenes) effects on health has increased in recent years, due to the growing evidence indicating that polyphenols are a major class of bioactive phytochemicals. Their consumption may play a role in the prevention of several chronic diseases as potent antioxidant properties, prevention of diseases induced by oxidative stress, and prevention of some specific cardiovascular (mainly high cholesterol levels, high blood pressure) and neurodegenerative diseases (such as Alzheimer’s or Parkinson’s, type II diabetes, cancers, urinary tract infections) [ 9 , 10 , 11 , 12 , 13 ]. However, the health effects of phenolic compounds are dependent on their type, quantity consumed, as well as on their bioavailability.…”
Section: Plant Bioactive Phenolic Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their abundance in vegetables and MAPs, the study of phenolic compounds’ (simple phenolics, coumarins, lignans, flavonoids, isoflavonoids, anthocyanins, proanthocyanidins, and stilbenes) effects on health has increased in recent years, due to the growing evidence indicating that polyphenols are a major class of bioactive phytochemicals. Their consumption may play a role in the prevention of several chronic diseases as potent antioxidant properties, prevention of diseases induced by oxidative stress, and prevention of some specific cardiovascular (mainly high cholesterol levels, high blood pressure) and neurodegenerative diseases (such as Alzheimer’s or Parkinson’s, type II diabetes, cancers, urinary tract infections) [ 9 , 10 , 11 , 12 , 13 ]. However, the health effects of phenolic compounds are dependent on their type, quantity consumed, as well as on their bioavailability.…”
Section: Plant Bioactive Phenolic Compoundsmentioning
confidence: 99%
“…The amount of total phenolic compounds is greater in dark vegetables, such as red kidney beans, black beans (Phaseolus vulgaris), and black gram (Vigna mango). Bravo [9] determined (by regarding dry matter, mg/100 g) the amount of total phenolic compounds in several vegetables such as black gram (540-1200), chickpeas , cowpea , common beans , green gram (440-800), pigeon peas (380-1710), Brussel sprouts (6)(7)(8)(9)(10)(11)(12)(13)(14)(15), cabbage (25), leek , onion , parsley , and celery (94).…”
Section: Plant Bioactive Phenolic Compoundsmentioning
confidence: 99%
“…Additionally, herbal teas and infusions are rich in natural antioxidants, mainly flavonoids: theaflavins, bis-flavanols, and fulvic acids. Their consumption has increased because they are recognized as having anticariogenic properties and antimicrobial and anticancer activity [85,86]. McCarthy et al [87] studied the antioxidant potential of plant extracts and compared them with synthetic antioxidants and vitamin E, incorporating them in pork.…”
Section: Natural Phenolic Antioxidants In Beveragesmentioning
confidence: 99%
“…Similar colour change tendency was observed at 40, 50 and 60°C, which was attributed to the effect of drying temperature; however, the formulation with stevia might have contributed to the change in colour difference compared to control (Kyoho skin powder). According to the latest review conducted by Vilela & Pinto (2019) reported the influence of drying temperature on tea chemical and sensory characteristics. The visual observation of Kyoho skin functional tea reported the red-green ( Figure S2) colour, which could be the contribution of Kyoho skin and stevia.…”
Section: Colour Measurementmentioning
confidence: 99%